Bioorthogonal pro-metabolites for profiling short chain fatty acylation. Issue 5 (20th December 2017) - Sinclair, Wilson R.; Shrimp, Jonathan H.; Zengeya, Thomas T.; Kulkarni, Rhushikesh A.; Garlick, Julie M.; Luecke, Hans; Worth, Andrew J.; Blair, Ian A.; Snyder, Nathaniel W.; Meier, Jordan L.
Abstract : A systematically designed panel of biorthogonal pro-metabolites was synthesized and evaluated as agents for tracing cellular short chain fatty acylation. Abstract : Short chain fatty acids (SCFAs) play a central role in health and disease. One function of these signaling molecules is to serve as precursors for short chain fatty acylation, a class of metabolically-derived posttranslational modifications (PTMs) that are established by lysine acetyltransferases (KATs) and lysine deacetylases (KDACs). Via this mechanism, short chain fatty acylation serves as an integrated reporter of metabolism as well as KAT and KDAC activity, and has the potential to illuminate the role of these processes in disease. However, few methods to study short chain fatty acylation exist. Here we report a bioorthogonal pro-metabolite strategy for profiling short chain fatty acylation in living cells. Inspired by the dietary component tributyrin, we synthesized a panel of ester-caged bioorthogonal short chain fatty acids. Cellular evaluation of these agents led to the discovery of an azido-ester that is metabolized to its cognate acyl-coenzyme A (CoA) and affords robust protein labeling profiles. We comprehensively characterize the metabolic dependence, toxicity, and histone deacetylase (HDAC) inhibitor sensitivity of these bioorthogonal pro-metabolites, and apply an optimized probe to identify novel candidate protein targets of short chain fatty acids in cells. Our studies showcase the utility of bioorthogonal pro-metabolites for unbiased profiling of cellular protein acylation, and suggest new approaches for studying the signaling functions of SCFAs in differentiation and disease.